The Role of Negotiation of Meaning in L2 Interactions:An Analysis from the Perspective of Long’s Interaction Hypothesis - Masrizal Masrizal (Universitas Syiah Kuala, 2014)
This study examines how negotiation of meaning contributes to second language interaction. The discussion in this study is based on Michael H. Long’s 1996 Interaction Hypothesis suggesting that environment contributes to the development of second language acquisition. Long proposes that environmental contributions to acquisition are mediated by selective attention and the learner’s processing capacity during negotiation for meaning. To support this belief, recent empirical studies are also presented in this article. Three negotiation for meaning strategies are discussed in this study to mirror and provide evidence for Long’s proposal, including several excerpts from conversations collected from daily natural conversations and other recorded sources. The strategies include (1) clarification requests, (2) confirmation checks, and (3) comprehension checks. The study has been able to prove that learner’s L2 acquisition takes advantage of environmental contributions mediated by selective attention and the learner’s developing L2 processing capacity brought together during negotiation of meaning.